Pierwsze polskie doświadczenia proweniencyjne z jodłą pospolitą Abies alba Mill. - Gunia, Stanisław; Szeligowski, Henryk; Łukaszewicz, Jan (Leśne Prace Badawcze, 2019)
Silver fir Abies alba Mill. provenance trials started in Poland a few years after Pavari (1951) proved that the origin of this tree species influences its genetic variability. Further confirmation came from provenance trials, which selected provenances for cultivation in Denmark and showed provenance-dependent genetic variability even within a relatively small area such as the Czech Republic. The Polish trial, started in 1960, compared 6 provenances from the West and Central Carpathian region (4 from Poland, 2 from Slovakia) and 3 from the Hercinic region (Czech Republic). The trial was established in the Experimental Forests of the Warsaw University of Life Sciences in Rogów, at the northern border of the natural silver fir range. Results from the nursery stage experiments proved the existence of latitudinal and altitudinal clines based on data for seed weight, height growth, number of terminal buds as well as bud and needle development. The Polish provenance ‘Stary Sącz’ and two Slovak provenances, ‘Čierný Váh’ and ‘Beňuš’, were early flushing, whereas the Polish provenance ‘Rogów’ behaved differently and was late flushing. Even at the nursery stage, the positive influence of tree selection on height growth and progeny characteristics of the two Czech provenances was evident. The Carpathian provenances were furthermore evaluated according to the index of cultivation and breeding: very good – ‘Rogów’; good ‘ŚPN (Świętokrzyski PN)’, ‘Stary Sącz’ and ‘Skarżysko’; poor – ‘Čierný Váh’ and ‘Beňuš’.